Security approach for instant messaging applications: viber as a case study - Mohammed Falih Kadhim; Adel Al-Janabi; Ahmed Hazim Alhilali; Nabeel Salih Ali (Institute of Advanced Engineering and Science, 2022)
A variety of internet-based applications are widely used in our animation activities because they provide free and useful services. These applications, such as Instant Messaging, can be run via the web, mobile, or computer-based devices. Therefore, the security and privacy of user data over these apps have been concerned in recent years because of sensitive and confidential information considerations. Consequently, many instant messaging applications, like Viber, have various security and privacy issues that need to be understood and resolved. Viber users reached 800 million, and they increased dramatically due to the efficient services that this app provides. Hence, a loophole in an application’s design may allow illegal access to the app and gain confidential and sensitive data. In this article, we proposed a security approach for Viber to safeguard user confidential data and sensitive information. The proposed approach involves two theoretical solutions: Short message service (SMS) authentication code and the physical hardware number to prevent illegal access to user data. Several scenarios are adopted to assess the proposed approach and achieve security and privacy for the user information.